Latin American modern architectures : ambiguous territories - Del Real, Patricio, 1966-; Gyger, Helen. (Routledge, 2013)
"Latin American Modern Architectures has thirteen new essays from a range of distinguished architectural historians to help you understand the region's rich and varied architecture. It will also introduce you to major projects that haven't been written about in English. A foreword by historian Kenneth Frampton sets the stage for essays on well-known architects, such as Luis Barragán and Félix Candela, which will show you unfamiliar aspects of their work, and for essays on the work of little-known architects, such as Lucio Costa and Joaquim Cardozo, which will spark your creativity. This book is your best source for historical and critical essays on a sampling of Latin America's diverse architecture, providing much-needed information on key case studies"--